Analysis of structural transformations in natural quartzites under the influence of gamma irradiation - Bereznyak, E.P.; Dikiy, N.P.; Kolodiy, I.V.; Medvedeva, E.P.; Khodyreva, Yu.S. (Вопросы атомной науки и техники, 2021)
Using the methods of IR spectroscopy, crystal-optical and XRD analysis the evolution of the structure of Ovruch deposit natural quartzites under the influence of γ-irradiation in the range of absorbed doses (Dabs = 10⁶…3.5⋅10⁷ Gy) has been researched. The elemental composition of natural quartzites was determined by the gamma activation method on a linear electron accelerator. It was found that as a result of irradiation the crystal structure of quartz, which forms the basis of quartzite, is improved due to radiation annealing of the defects in the initial structure. At the same time crystallization of amorphous silica, which fringes large grains of quartz, occurs with its transformation into fine-crystalline quartz. These processes do not lead to cracking in the quartzite rock. Obtained data indicates a high radiation resistance of the Ovruch deposit quartzites and confirms the prospects of using this geological formation as a natural barrier for the construction of radioactive waste long-term storage. За допомогою методів ІЧ-спектроскопії, кристалооптичного та рентгеноструктурного аналізів вивчена еволюція структури природних кварцитів Овруцького родовища під впливом γ-опромінення в інтервалі поглинених доз Dпогл = 10⁶…3,5⋅10⁷Гр. Визначений елементний склад природних кварцитів методом гаммаактивації на лінійному прискорювачі електронів. Встановлено, що в результаті опромінення кристалічна структура кварцу, що становить основу кварциту, вдосконалюється внаслідок радіаційного відпалу дефектів вихідної структури. Одночасно відбувається кристалізація аморфного кремнезему, що окаймляє великі зерна кварцу, з перетворенням його в дрібнокристалічний кварц. Ці процеси не призводять до утворення тріщин у кварцитовій породі. Отримані дані свідчать про високу радіаційну стійкість кварцитів Овруцького родовища і підтверджують перспективність використання даної геологічної формації як природного бар'єру для спорудження довготривалого сховища радіоактивних відходів. С помощью методов ИК-спектроскопии, кристаллооптического и рентгеноструктурного анализов изучена эволюция структуры природных кварцитов Овручского месторождения под влиянием облучения γ-квантами в интервале поглощенных доз Dпогл = 10⁶…3,5⋅10⁷Гр. Определен элементный состав природных кварцитов методом гамма-активации на линейном ускорителе электронов. Установлено, что в результате облучения кристаллическая структура кварца, составляющего основу кварцита, совершенствуется вследствие радиационного отжига дефектов исходной структуры. Одновременно происходит кристаллизация аморфного кремнезема, окаймляющего крупные зерна кварца, с превращением его в мелкокристаллический кварц. Эти процессы не приводят к трещинообразованию в кварцитовой породе. Полученные данные свидетельствуют о высокой радиационной стойкости кварцитов Овручского месторождения и подтверждают перспективность использования данной геологической формации в качестве природного барьера для сооружения долговременного хранилища радиоактивных отходов.